Personal and area exposure assessment at a stainless steel fabrication facility: an evaluation of inhalable, time-resolved PM10, and bioavailable airborne metals. Issue 2 (1st February 2021) - Newton, Ashley; Adams, Karin; Serdar, Berrin; Dickinson, L. Miriam; Koehler, Kirsten
Abstract: This study describes a comprehensive exposure assessment in a stainless steel welding facility, measuring personal inhalable PM and metals, time-resolved PM10 area metals, and the bioavailable fraction of area inhalable metals. Eighteen participants wore personal inhalable samplers for two, nonconsecutive shifts. Area inhalable samplers and a time-resolved PM10 X-ray fluorescence spectrometer were used in different work areas each sampling day. Inhalable and bioavailable metals were analyzed using inductively coupled plasma mass spectrometry (ICP-MS). Median exposures to chromium, nickel, and manganese across all measured shifts were 66 (range: 13–300) μg/m 3, 29 (5.7–132) μg/m 3, and 22 (1.5–119) μg/m 3, respectively. Most exposure variation was seen between workers ( 0.79 < ICC < 0.55 ), although cobalt and inhalable PM showed most variation within workers. Manganese was the most bioavailable metal from the inhalable size fraction (16 ± 3%), and chromium and nickel were 1.2 ± 0.08% and 2.6 ± 1.2% bioavailable, respectively. This comprehensive approach to welding-fume exposure assessment can allow for targeted approaches to controlling exposures based not only on individual measurements, but also on metal-specific measures and assessments of bioavailability.